Identifikasi Tepung Ampas Kelapa Terhadap Kadar Proksimat Menggunakan Metode Pengeringan Oven - Rousmaliana Rousmaliana; Septiani Septiani (Sarana Ilmu Indonesia (salnesia), 2019)
Coconut pulp is a byproduct of making coconut milk. The process of making coconut pulp flour is not widely used. This study aimed to analyze the difference in proximate levels (water, ash, protein, fat, carbohydrates, and total fiber) from organoleptic test results. This study used an experimental design with a Completely Randomized Design to find out the best quality coconut pulp flour that contains nutritional value. Formula T57 was the formula chosen from the organoleptic test with 5.70% water content, 7.30% fat, 4.91% protein, 0.34% ash content, 2.37% fiber, and 81.75% carbohydrate. It is necessary to test the shelf life of the selected formula.